Two new species of Cercyon (Clinocercyon) from Russian Far East (Coleoptera: Hydrophilidae) - Ryndevich, Sergey K.; Prokin, Alexander A. (Zootaxa, 2017)
Two new species, Cercyon retius sp. nov. and C. primoricus sp. nov., both belonging to the subgenus Clinocercyon, are described from the Russian Far East. A key to the identification of the six known Palearctic species of the subgenus is given. Both new species are illustrated by photographs of habitus and some morphological characters and by drawings of male genitalia. Within the subgenus Clinocercyon, the new species are most similar to C. conjiciens (Walker) and to the two Japanese species (C. aequalis Sharp and C. rubicundus Sharp). With the inclusion of these two new species, the fauna of Cercyon in Russia now comprises 47 species from 5 subgenera.